Health system barriers to the implementation of the national action plan to combat antimicrobial resistance in Vietnam: a scoping review - Giang N. Pham; Tho T. H. Dang; Thu-Anh Nguyen; Shukry Zawahir; Hien T. T. Le; Joel Negin; Carmen Huckel Schneider; Greg J. Fox (Antimicrobial Resistance and Infection Control, 2024)
Abstract Background Vietnam is among 11 countries in the Western Pacific region that has developed a National Action Plan for Antimicrobial Resistance (NAPCA). Methods This scoping review characterises health system barriers to the implementation of the Vietnam NAPCA, with reference to the WHO Health Systems Framework. Results Over 7 years, between 2013 and 2020, the Ministry of Health (MOH) of Vietnam has been implementing activities to achieve the six NAPCA objectives. They include revision of regulations needed for antimicrobial resistance (AMR) prevention programs; formation and operation of national management bodies; improvement of antimicrobial stewardship (AMS) in hospitals; maintenance of surveillance systems for AMR; provision of trainings on AMR and antibiotics use to doctors and pharmacists; and organization of nation-wide educational campaigns. Limited cooperation between MOH management bodies, shortages of human resource at all health system levels, a low degree of agreement between national and hospital guidelines on antibiotic use, low capability in the domestic supply of standardised drugs, and unequal training opportunities for lower-level health professionals present ongoing challenges. Actions suggested for the next period of the NAPCA include a final review of what has been achieved by the plan so far and evaluating the effectiveness of the different components of the plan. Different options on how to improve coordination across sectors in the development of a new NAPCA should be put forward. Conclusions The 6-year implementation of the Vietnam NAPCA has yielded valuable lessons for AMS in Vietnam, guiding the development of future national plans, with a central focus on scaling up AMS in hospitals and promoting community AMS programs to combat AMR.